IDENTIFIKASI SEKTOR EKONOMI UNGGULAN DI KABUPATEN MIMIKA PROVINSI PAPUA - Abu Bakar (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2017)
The aims of this research are: (1) analyze the growth classification of economic sectors in the Mimika Regency; (2) analyze the basic sector of the economy in the Mimika Regency; (3) analyzing the share and shifts in the economy sector Mimika Regency.This study uses secondary data obtained from BPS-StatisticsPapua Province, BPS-Statistics Mimika, and Department of Planning and Regional Development Mimika. Data were analyzed using analysis Klassen Typology, Location Quotient, and Shift-Share analysis.The results of this research show that: (1) Sector classified as andeveloped sector in the Mimika Regency is Electricity and Gas sector, sector of Accomodation, Food and Beverages. (2) Sectors is a basic sector in Mimika is the sector of Agriculture, Forestry and Fishery, sector of Electricity and Gas, sector Water, Waste Management, cesspit and recycling, Construction sector, the sector of Wholesale and Retail trade, Cars and Motorcycles Reparations, sectors Transportation and Warehousing, sector of Accommodation, Food and Beverages, sector Information and Communications, Fnance and insurance sector, Real Estate, Public administration, defense, and compulsory social security, and sector Other Services. (3) The sectors that have competitive advantages (D) in Mimika are sectors of Manufacturing industry, Electricity and Gas sector, sector of Accommodation, food and beverages. (4) By combining the results of the analysis Klassen Typology, Location Quotient, and Shift Share, then the sectors which are the leading sectors in the Mimika Regency is the Electricity and Gas sector, sector of Accommodation, food and beverages